Hubungan Kualitas Tidur Dengan Kejadian Hipertensi Pada Lansia di Desa Sukadaya Kecamatan Sukawangi Kabupaten Bekasi 2023 - Ananda, Galuh; I Ratnah; Rotua Suriany Simamora (Rena Cipta Mandiri, 2024)
Hypertension is a non-communicable disease caused by various risk factors. One of the factors that causes hypertension is sleep quality. Sleep quality is a process when a person is sleeping, which is done to maintain a state of sleep and to obtain the appropriate Rapid Eye Movement (REM) and Non Rapid Eye Movement (NREM) stages. A person's habit of not sleeping enough or having poor quality sleep can increase the risk of increased blood pressure or hypertension. The aim of this research is to determine the relationship between sleep quality in the elderly and the incidence of hypertension in the elderly in Sukadaya Village, Sukawangi District, Bekasi Regency in 2023. The type of research used is quantitative research with observational methods (cross sectional), a sample of 170 people aged 60 years. tThe sampling technique uses simple random sampling. Sleep quality data was collected using the PSQI questionnaire directly and blood pressure measurements. This research stated that the sleep quality of the respondents was in the poor category, 86 respondents 50.6%, and the blood pressure of the respondents was categorized as high, 98 respondents 57.6%. The statistical test results showed that the p-value = 0.000 (α < 0.05). So this shows that H0 is rejected, which means that there is a relationship between sleep quality and the incidence of hypertension in the elderly in Sukadaya Sukawangi Bekasi 2023.